Pola Asuh Islami Orang Tua dalam Mencegah Timbulnya Perilaku LGBT Sejak Usia Dini - Eka Yanuarti (IAIN Ponorogo, 2019)
Abstract: Lack of Parents attention due to children social lives allow the emergence of abnormal behavior or promiscuity. Like a case of LGBT (Lesbian Gay Bisexual and Transgender) which is raised from various factors. This article contains a descriptive analytics method in illustrating the parenting style to avoid the LGBT behavior from an early age. Furthermore, the conclusion of this paper is Islamic parenting style in preventing the LGBT behavior from an early age can be initiated by providing religionvalue, moral education, social education, social supervision and criticism, environment education and sexual education. Moreover, Islamic parenting can be carried out with the pattern taught by the Prophet Muhammad SAW, such as separating bedroom, growing a self-esteem in children and instilling a spirit of masculinity and femininity from an early age. ملخص: عدم اهتمام الوالدين بتفاعل الولد، يسمح بظهور العلاقات السيئة مع الولد. مثل ظهر تفاعل مثليات ومثليون جنسيا وثنائيي الجنس والمخنثين بسبب عوامل مختلفة. تحتوي هذه الكتابة على تحليلي وصفي من المراجع المختلفة تناقش عن أسلوب الرعاية الإسلامية الوالدين في منع سلوك مثليات ومثليون جنسيا وثنائيي الجنس والمخنثين من سن مبكرة. الاستنتاج هو أن أسلوب الرعاية الإسلامية الوالدين في منع سلوك مثليات ومثليون جنسيا وثنائيي الجنس والمخنثين من سن مبكرة يمكن أن تبدأ من خلال توفير التعليم الإيمان، والتعليم الأخلاق، والتعليم الاجتماعي، ثم الإشراف والنقد الاجتماعي، والتعليم حول حماية البيئة والتربية الجنسية. يمكن أن ينقذ أسلوب رعاية الإسلامية بالأساليب التي تدرسه النبي محمد صلى الله عليه وسلم منها بفصل السرير، وغرس الحياء على الولد، وغرس روح الرجولة والأنوثة منذ سن مبكرة.